2019
DOI: 10.1016/j.yjmcc.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput ratiometric method for imaging hypertrophic growth in cultured primary cardiac myocytes

Abstract: Maladaptive hypertrophy of cardiac myocytes increases the risk of heart failure. The underlying signaling can be triggered and interrogated in cultured neonatal ventricular myocytes (NRVMs) using sophisticated pharmacological and genetic techniques. However, the methods for quantifying cell growth are, by comparison, inadequate. The lack of quantitative, calibratable and computationally-inexpensive high-throughput technology has limited the scope for using cultured myocytes in large-scale analyses. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Myocyte isolation and culture was performed as described previously [ 42 ]. Animals were killed by cervical dislocation according to Schedule 1 of the Animals (Scientific Procedures) Acts 1986.…”
Section: Methodsmentioning
confidence: 99%
“…Myocyte isolation and culture was performed as described previously [ 42 ]. Animals were killed by cervical dislocation according to Schedule 1 of the Animals (Scientific Procedures) Acts 1986.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of hypertrophy by all of these chemical agents show a similar modeling time of 24 h, which may be extended to 48 h depending on the used cell type ( Zhang et al, 2016 ; Zlabinger et al, 2019 ; Zhao et al, 2020 ). The concentration needs to be optimized by testing different dilutions before the experiment, however the general used concentrations are 20 µM phenylephrine ( Gelinas et al, 2018 ), 100 nM angiotensin II ( Zlabinger et al, 2019 ), 10 μM isoproterenol ( Zhang et al, 2016 ), and 10 nM endothelin-1 ( Loonat et al, 2019 ).…”
Section: Methods Of Cardiac Hypertrophy Inductionmentioning
confidence: 99%
“…This development combined with the relative paucity of direct treatment options for cardiac hypertrophy makes continued research and the identification of novel therapeutic target molecules absolutely vital. Cardiac hypertrophy is an adaptive process which develops in response to physiological but also pathological processes, leading to heart muscle and cell hypertrophic growth with increased rigidity of the heart structures, and impaired diastolic function leading to heart failure with preserved ejection fraction (HFpEF) ( Loonat et al, 2019 ; Zhao et al, 2020 ). Hypertrophic growth involves cardiomyocyte enlargement rather than division, as adult cardiomyocytes have lost the ability to divide ( Porrello et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our and other laboratories have demonstrated a differential activity and/or expression of cardiac NBC isoform in different in vivo hypertrophy models [16][17][18][19] . Moreover, we showed that the activity of NBCe1 is decreased while NBCn1 is over-expressed and over-activated in the hypertrophied myocytes of spontaneous hypertensive rats (SHR) 17 .…”
Section: Introductionmentioning
confidence: 99%